Arisan sebagai Sarana Komunikasi Antar Pribadi dalam Menjalin Silaturrahim - Ahmad Rofi; Fitri Komala Sari (STID DI AL-HIKMAH, 2016)
This study aims to determine the interpersonal communication is done in a social gathering activities so as to be instrumental in establishing silaturrahim in RT 009 RW 018 villages Duren Jaya, East Bekasi. This research was carried directly into the field survey method to obtain primary data and secondary. In addition to interviews, the researchers also conducted a series of documentation on the activities of the residents do. This study uses descriptive qualitative research. The number of respondents was 9 members gathering. Data were obtained from interviews, observation and documentation then do the processing and analysis. Instrument used in this research is interview guides, worksheets and camera phone.